A REVIEW ON THE USE OF DENTAL LOUPES AND OPERATING MICROSCOPE IN ENDODONTICS - Majid Mohammad Alshammari1*, Faleh Hamad Alshammari 2, Nasser Siran Alharbi3, Yazeed Aied Alrawili4, Raid Marhj Aldhafeeri5, Jaza Hameed Aldhfeeri 6, Mohammed Khalif Aldafeeri7 (Chelonian Research Foundation, 2022)
Having a clear accessibility and vision in Endodontic therapy was a challenging issue in the history until the development of various magnification tools. These tools have improved the prognosis of root canal treatment and made it possible to treat some difficult cases that were impossible to treat without magnification. This article highlights the use of dental loupes and operating microscope and their merits and demerits. Also, the stages of magnification are needed for various dental procedures. Source: “EBSCO”, “Medline” and “PubMed” databases Keywords: Endodontic, operating microscope, magnification, and dental loupes